Ethnobotanical survey of medicinal plants used by nomadic peoples in the Algerian steppe. (12th June 2018) - Miara, Mohamed Djamel; Bendif, Hamdi; Ait Hammou, Mohammed; Teixidor-Toneu, Irene
Abstract: Ethnopharmacological relevance: This study is the first ethnobotanical survey focusing on the herbal medicines traditionally used by the nomadic community of the Algerian steppe, identifying new medicinal plants and uses from one of the most characteristic indigenous populations in Algeria. Moreover, the study contributes to the understanding of transmission of medicinal plant knowledge in the Mediterranean basin. Aim of the study: This work aims to document the phytotherapeutical knowledge and practice of the nomadic community of the Algerian steppe, and compare it with neighbouring sedentary populations and Mediterranean historical texts. Through this, the study strives to evaluate processes of transmission of knowledge among this population, for whom written sources have been largely unavailable. Methods: Ethnobotanical surveys were carried out during two years (2015–2017). In total, 73 informants from nomadic populations were interviewed in several steppe regions including areas in the administrative departments of Tiaret, Saida, Naama, Djelfa and M'sila. Structured interviews about medicinal plant knowledge were combined with guided tours with the informants. Prior informed consent was always obtained. The surveys allowed for the collection of sociodemographic data and traditional knowledge about medicinal plants and their uses. Informant Consensus Factor (FIC ) was calculated to evaluate agreement among informants. Results were compared to existing literature to evaluate similarities between this nomadic medicinal flora, that of neighbouring communities and historical texts and identify new plant citations and uses. Results: Among Algerian nomadic communities, herbal remedies are used mostly by women and elders, who are often illiterate. We identified 97 taxa of medicinal plants belonging to 42 botanical families, importantly Lamiaceae, Asteraceae and Apiaceae, like in neighbouring communities. The most common plant parts and method of preparation are also shared with neighbouring populations. New uses are described for 25 known medicinal taxa, and nine species with undocumented medicinal uses in recent literature have been reported. However, some of these have been reported in Mediterranean materia medica . In total, 60% of the medicinal plant diversity used by Algerian nomads are well-known plants of the Mediterranean ethnopharmacological heritage. Conclusion: This study highlights the importance of traditional medicine for Algerian nomad communities. This indigenous population has specific knowledge about plants from their steppe environment, but also shares a pool of knowledge with sedentary Algerian populations and Mediterranean people as a whole. Our research shows that a common North African and Mediterranean ethnobotanical heritage exists. Graphical abstract: fx1